2020
DOI: 10.22271/chemi.2020.v8.i4ai.10085
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis over environments in linseed (Linum usitatissimum L.) varieties

Abstract: A field experiment was conducted during Rabi season of 2015-16. To study the stability analysis of yield and its component traits in 20 genotypes of linseed i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
2
0
0
Order By: Relevance
“…1, 6 and 8 recorded the lowest value of the mean of stability than the mean of the genotypes included in the study, and that the value of α was higher than zero and the significance of α> 0 and λ = 1. This results agrees with (Yadav et al, 2014).…”
Section: Seed Yield (Plantg -1 )supporting
confidence: 93%
See 1 more Smart Citation
“…1, 6 and 8 recorded the lowest value of the mean of stability than the mean of the genotypes included in the study, and that the value of α was higher than zero and the significance of α> 0 and λ = 1. This results agrees with (Yadav et al, 2014).…”
Section: Seed Yield (Plantg -1 )supporting
confidence: 93%
“…α does not differ significantly from zero 0 = α and the extent of is not significantly different from one = 1, and this means that this genotype has moderate stability, Genotypes 3, 4 and 5 showed that they have a stability degree above the mean 0> α and λ=1, which means that these genotypes are above average stability and their stability is confirmed and respond even to poor environments, While the genotypes 6, 7, and 8 were less stability than the mean 0 <α and 1 = λ that the values of α were significantly higher than zero and λ=1, this means that these genotypes are less stability than the average of the genotypes included in the study. As for the genotype (2), it was not stable according to (Tai, 1971) because the value of λ =1, this result agreed with what was stated by (Yadav et al, 2014).…”
Section: Plant Height (Cm)supporting
confidence: 87%